Gendered marginalization of disabled bodies: understanding 'marginalization' as (perhaps) the most dangerous form of oppression - Karim, Shuchi (BRAC University, 2016)
The essay applies Iris Marion Young's discussion of marginalization as a form of oppression suffered differentially by specific social groups, in relation to women with disabilities. It draws on Young's frame, which desegregates 'oppression', taking it away from theories overarching and systematic structures of racism for example, or patriarchy, presenting instead the concept of oppressed groups as overlapping rather than distinct, and of oppression as multiplex and differentially affecting different social groups. The essay considers women with disabilities in terms of their vulnerability to marginalization, one of Young's five types of oppression.